Recent Insights into Nanoparticulate Carrier Systems of Curcumin and its Clinical Perspective in the Management of Various Health Issues - Harwansh, Ranjit K.; Yadav, Mukul; Deshmukh, Rohitas; Rahman, Akhlaquer (Current Pharmaceutical Design, 2023)
Curcumin is a potent bioactive compound of Curcuma longa. Curcumin comprises a broad spectrum of biological activities, including hepatoprotective, anticancer, antimicrobial, anti-inflammatory, antitumor, anti- oxidant, etc. However, its low aqueous solubility, rapid excretion, and poor bioavailability restricted its therapeutic uses. To resolve these issues, novel nano-systems have now been developed to increase the bioactivity and bioavailability of curcumin by lowering the particle size, altering the surface, and increasing the efficacy of its encapsulation with various nanocarriers. Nanotechnology-based treatments can broaden the outlook for individuals with critical conditions. This article explores curcumin-based nanoparticulate carrier systems that should be employed to overcome this natural ingredient's inherent limitations. These nanocarriers also provide physical and chemical stability by encapsulating the drug into the core or matrix of the lipids or polymers. Nanotechnologists developed curcumin-encapsulated various nanoparticulate systems, including solid lipidic nanoparticles, polymeric nanoparticles, nano-structured lipid carriers, polymer conjugates, etc., to improve curcumin bioavailability and boost the sustained release of curcumin to target cells.
Keywords: Curcumin